2021
DOI: 10.1101/2021.03.09.21253184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased mortality among individuals hospitalised with COVID-19 during the second wave in South Africa

Abstract: Introduction: South Africa experienced its first wave of COVID-19 peaking in mid-July 2020 and a larger second wave peaking in January 2021, in which the SARS-CoV-2 501Y.V2 lineage predominated. We aimed to compare in-hospital mortality and other patient characteristics between the first and second waves of COVID-19. Methods: We analysed data from the DATCOV national active surveillance system for COVID-19 hospitalisations. We defined four wave periods using incidence risk for hospitalisation, pre-wave 1, wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 35 publications
4
62
1
1
Order By: Relevance
“…If individuals in low-income communities require in-patient treatment, they are more likely to access the relatively under-resourced public health sector. An analysis of COVID-19 in-hospital mortality in South Africa, found that admission to a public sector compared to a private sector facility was associated with increased risk of mortality (adjusted odds ratio of 1.6; 95% CI 1.4-1.8) 22 . This may be due to later presentations to hospital, as well as differences in access to and unequal availability of critical care and other specialized resources or interventions in the public sector.…”
Section: Discussionmentioning
confidence: 99%
“…If individuals in low-income communities require in-patient treatment, they are more likely to access the relatively under-resourced public health sector. An analysis of COVID-19 in-hospital mortality in South Africa, found that admission to a public sector compared to a private sector facility was associated with increased risk of mortality (adjusted odds ratio of 1.6; 95% CI 1.4-1.8) 22 . This may be due to later presentations to hospital, as well as differences in access to and unequal availability of critical care and other specialized resources or interventions in the public sector.…”
Section: Discussionmentioning
confidence: 99%
“…In Südafrika lag die Krankenhausletalität während der zweiten Welle (Höhepunkt Januar 2021), die – im Gegensatz zur ersten Welle (Höhepunkt Juli 2020) – fast vollständig auf der Beta-Variante beruhte, um 20 % höher als während der ersten Welle. Die höhere Letalität war dabei nicht durch die höhere Zahl der Krankenhauseinweisungen erklärt [ 24 ].…”
Section: Mutante „Beta“ (B1351 Oder „Südafrikanische Mutante“)unclassified
“…6 The disease mortality has been increased in these countries after new variants were developed. [7][8][9][10] An increased risk of transmissibility, hospitalization and death associated with the B.1.1.7 variant was reported by number of authors. 8,[11][12][13][14][15][16] The B.1.351 variant was found to have an increased transmissibility and immune escape, 17 and was estimated to be 50% more transmissible than preexisting variants.…”
Section: Introductionmentioning
confidence: 99%